Analysis of the Influence of Work Discipline, Performance Allowances, Work Conflict and Workload on Employee Performance at the Balai of the Ministry of Public Works and Public Housing Jayapura Region - Yuyun Vitaloka; Meutia Meutia; Zainur Hidayah (International Journal Labs, 2023)
This study aims to analyze the effect of work discipline, performance allowances, work conflict, and workload on employee performance at the Jayapura Region Hall of the Ministry of Public Works and Public Housing with a sample of 50 respondents. Data collection methods using questionnaires and interviews. The analysis method used is multiple linear analysis and t-test. The results of this study indicate that work discipline and performance allowances have a significant effect on employee performance, while work conflict and workload do not have a significant effect on employee performance at the Balai of the Ministry of Public Works and Public Housing Jayapura Region. The results of this study are expected to be a reference and insight for organizational management in designing human resource development strategies and improving employee performance. In addition, this research also contributes to further research in the field of human resource management and understanding the factors that affect employee performance.